Exosomes: new targets for understanding axon guidance in the developing central nervous system - Liu, Mingyu; Teng, Teng (Frontiers in Cell and Developmental Biology, 2025)
Axon guidance is a key event in neural circuit development that drives the correct targeting of axons to their targets through long distances and unique patterns. Exosomes, extracellular vesicles that are smaller than 100 nm, are secreted by most cell types in the brain. Regulation of cell-cell communication, neuroregeneration, and synapse formation by exosomes have been extensively studied. However, the interaction between exosomes and axon guidance molecules is poorly understood. This review summarizes the relationship between exosomes and canonical and non-canonical guidance cues and hypothesizes a possible model for exosomes mediating axon guidance between cells. The roles of exosomes in axon outgrowth, regeneration, and neurodevelopmental disorders are also reviewed, to discuss exosome-guidance interactions as potential clinical therapeutic targets.